Short Communication: Leaf architectural analysis of taxonomically confusing coffee species: Coffea liberica and Coffea liberica var. dewevrei - ALCONA MAE P BALTAZAR; INOCENCIO Jr E BUOT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Baltazar AMP, Buot JrIE. 2019. Short Communication: Leaf architectural analysis of taxonomically confusing coffee species: Coffea liberica and Coffea liberica var. dewevrei. Biodiversitas 20: 1560-1567. Coffee is considered as one of the most important crops. The Philippines is known to produce four coffee varieties namely: Arabica (Coffea arabica), Robusta (Coffea canephora), Excelsa (Coffea liberica var. dewevrei) and Liberica (Coffea liberica). Further, the taxonomy of C. liberica and C. liberica var. dewevrei is still unclear. Since its earliest publication, the relationship of the two taxa have been confusing many taxonomists and also farmers. The status of the two confusing taxa are still under discussions due to contradicting evidence inferred from morphological and molecular data. The two taxa have been claimed as separated species but the markers are considered inconsistent in the field. This study has tried to examine the leaf architectural characters of both species as these have been known to be genetically fixed. Leaf samples of each species including C. canephora (outgroup) were collected and examined. Results showed that the two taxa were found to be different in laminar size, domatia distribution, major secondary attachment, and intercostal tertiary veins. Cluster analysis revealed that they are grouped separately. However, the rank of C. liberica var. dewevrei cannot be decided yet until further taxonomic study, particularly on the anatomy and distribution pattern of domatia, is completed.